Can Music Increase Empathy? Interpreting Musical Experience Through the Empathizing–Systemizing (E-S) Theory: Implications for Autism - Greenberg, David M.; Rentfrow, Peter J.; Baron-Cohen, Simon (Empirical Musicology Review, 2015)
Recent research has provided evidence that musical interaction can promote empathy. Yet little is known about the underlying intrapersonal and social psychological processes that are involved when this occurs. For example, which types of music increase empathy and which types decrease it; what role, if any, does empathy play in determining individual differences in musical preference, perception, and performance; or, how do these psychological underpinnings help explain the musical experiences of people with autism spectrum conditions (ASC). To address these questions we employ the Empathizing–Systemizing (E-S) theory as a fruitful framework in which to understand these music-related phenomena. Specifically, we explore how individual differences in musical preference, perception, and performance can be explained by E-S theory. We provide examples from open-ended descriptions of strong musical experiences to demonstrate the ways in which empathy and music inter-relate. Importantly, we discuss the implications for the study of autism, and for how music therapists and clinicians can use music as a tool in their work with individuals diagnosed with ASC.